2014
DOI: 10.1117/12.2044670
|View full text |Cite
|
Sign up to set email alerts
|

Instantaneous wavenumber estimation for damage quantification in layered plate structures

Abstract: Guided wavefield detection is at the basis of a number of promising techniques for the identification and the characterization of damage in plate structures. Among the processing techniques proposed, the estimation of instantaneous and local wavenumbers can lead to effective metrics that quantify the extent of delaminations in composite plates. This paper illustrates the application of instantaneous and local wavenumber damage quantification techniques for high frequency guided wave interrogation. The proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…It was also observed that there is no converted S0 mode when the A0 mode encounters delaminations located at a symmetric interface. The combination of several damage mechanisms for realistic impact damage in laminated composites makes the accurate modelling more challenging, with limited studies employing full 3D analysis 24 . Recent work 25 has demonstrated that 3D simulations can accurately predict the scattering characteristics of guided waves at a circular-shaped delamination.…”
Section: Introductionmentioning
confidence: 99%
“…It was also observed that there is no converted S0 mode when the A0 mode encounters delaminations located at a symmetric interface. The combination of several damage mechanisms for realistic impact damage in laminated composites makes the accurate modelling more challenging, with limited studies employing full 3D analysis 24 . Recent work 25 has demonstrated that 3D simulations can accurately predict the scattering characteristics of guided waves at a circular-shaped delamination.…”
Section: Introductionmentioning
confidence: 99%
“…From the literature, the potential for the impact damage in composites has been demonstrated, but the interaction of the guided waves with the complex and multi-mode impact damage requires improved understanding. It is quite challenging for producing an accurate modelling of a real impact employing full 3D analysis [17]. Varieties of factors affect the propagation and scattering of guided waves in composite structures and could lead to inaccurate monitoring and defect detection results.…”
Section: Introductionmentioning
confidence: 99%
“…depth) coordinates of defects in composites. In Mesnil et al, 17 the authors show a first collaborative work resulting in an automatic feature extraction process relying on the Smooth Sparse Decomposition 18 (SSD) algorithm, which is a flexible defect detection technique to automatically separate the defect component from the background, based on the different spatial structure of each component.…”
Section: Introductionmentioning
confidence: 99%